1987
DOI: 10.1089/dna.1987.6.81
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Transfection and Expression of Reconstituted DNA-Protein Complexes in Eukaryotic Cells

Abstract: Transfection of foreign DNA into eukaryotic cells has become an important tool in molecular biology. Based on the results of previous studies of the core structure of human adenoviruses, we have developed a novel transfection method. The procedure involves the in vitro reconstitution of foreign DNA-of viral or other origins-with the major core protein VII of adenovirus type 2 (Ad2) or protamine from salmon sperm. Both proteins are rich in basic amino acids and appear to share structural features. The DNA-prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…221 Similar to whole Ad, gene transfer was inhibited by WGA, suggesting that interaction with the NPC, likely via the hexon, enables gene transfer. The core protein VII of Ad2, which normally binds viral genomic DNA and facilitates its transport into the nucleus, 222 enabled nuclear association of about 40% of applied DNA by 2-4 h after transfection, as distinguished by subcellular fractionation, 222 though it was unclear whether the DNA was actually transported into the nucleus. Vpr of HIV has both DNA condensing and nuclear targeting features that can facilitate nonviral gene transfer.…”
Section: Cellular and Molecular Determinantsmentioning
confidence: 99%
“…221 Similar to whole Ad, gene transfer was inhibited by WGA, suggesting that interaction with the NPC, likely via the hexon, enables gene transfer. The core protein VII of Ad2, which normally binds viral genomic DNA and facilitates its transport into the nucleus, 222 enabled nuclear association of about 40% of applied DNA by 2-4 h after transfection, as distinguished by subcellular fractionation, 222 though it was unclear whether the DNA was actually transported into the nucleus. Vpr of HIV has both DNA condensing and nuclear targeting features that can facilitate nonviral gene transfer.…”
Section: Cellular and Molecular Determinantsmentioning
confidence: 99%
“…Other cationic peptides with a less canonical NLS sequence (with regard to that of SV40 antigen T), such as protamine (Wienhues et al, 1987), histone H2 (Balicki et al, 2002) and melittin-derived peptides , have been shown to display DNA compaction and enhanced in vitro transfection efficiency properties.…”
Section: Non-covalent Association Of Dna With Nls Sequence-bearing Symentioning
confidence: 99%
“…Whether the increased thermostability pertains to the entire adenovirus structure or just the core is uncertain. It is possible that a more thermostable core alone would produce the results we obtained since a DNA-pVII complex by itself has transfection capability (Wienhues et al, 1987). Such "nonviral" transduction would likely contribute to the increased t.u.…”
Section: Visualization Ofmentioning
confidence: 94%